Graphitic-C3N4/γ-Al2O3 composite catalyst for synthesis of 5-(Hydroxymethyl) furfural from d-Glucose - Kirdant, Swapnali P.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (Energy & Fuels, 2025)
Currently, the synthesis of 5-hydroxymethylfurfural (5-HMF), with high yields and selectivity from different renewable sources, is an important focus in the biomass conversion area. In the present study, a g-C3N4/gamma-Al2O3(1:1) composite catalyst was prepared using graphitic carbon nitride (g-C3N4) and acidic gamma-alumina (gamma-Al2O3), which was evaluated for its catalytic activity in converting sugars, mainly glucose, to 5-HMF. In the g-C3N4/gamma-Al2O3(1:1) catalyst, N-containing groups on g-C3N4 provided basicity and gamma-Al2O3 provided Lewis acidity to the catalyst. The g-C3N4/gamma-Al2O3(1:1) composite catalyst showed superior activity for 5-HMF synthesis compared to gamma-Al2O3 and g-C3N4 alone. The increased acidic and basic properties of the g-C3N4/gamma-Al2O3(1:1) catalyst significantly influenced both glucose-to-fructose isomerization and dehydration of fructose to HMF by increasing the yield of 5-HMF. In addition, the solvent DMSO:water also played an important role in the one-pot conversion of glucose to HMF by minimizing side reactions, which significantly improved the 5-HMF yield. The reaction was optimized for various solvents, temperatures, and catalyst concentrations to get a maximum yield of 91% from glucose with >99% selectivity of crude 5-HMF. Other sugars like fructose, sucrose, and lactose also provided good yields of 5-HMF. The g-C3N4/gamma-Al2O3(1:1) catalyst was stable and was effectively reused for up to four cycles.